PENGEMBANGAN MODUL BERBASIS PEMECAHAN MASALAH PADA MATERI PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL UNTUK SISWA KELAS VII SMPN 12 PADANG - Salmi, Zuhrina - (Pendidikan Matematika, 2014)
The background of the research is a textbook teaching material which has not been able to train the students to solve the problems. The learning stages of solving problem-based math module of the research follow the problem solving strategy steps, i.e, (1) understanding the problem, (2) planning the solution, (3) solving the problem based on the planning and (4) doing the recheck. The development model referenced is the model of 4D development consisting 4 stages. They are defining stage, desingning stage, developing stage and disseminating stage. The result of module validity test by validator show that the module is very valid criteria, i.e,3.32. It is reviewed from the aspects of content, presentation, language, readability and graph. The teacher practical test result show that the module is in the practical criteria, i.e,73.33% and the student practical test result show that the module is in the very practical criteria, i.e, 81.06%.